2021
DOI: 10.1111/head.14098
|View full text |Cite
|
Sign up to set email alerts
|

Functional difficulties mediate the association between exposure to adverse childhood experiences and headaches among children: Findings from a population‐based study

Abstract: Background Adverse childhood experiences (ACEs) are commonly observed in the general population and often have lasting neurological and physiological effects. Previous studies have found links between exposure to ACEs, headaches, and functional difficulties in adults. However, little is known about the mechanisms through which exposure to ACEs is associated with headaches among children. Objective To examine the association between exposure to ACEs and headaches in children, and whether functional difficulties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 77 publications
2
2
0
Order By: Relevance
“…Similarly, others have observed cross-sectional relationships between the number of ACEs and headache but did not investigate migraine independently. 5,6 Within the present study, the magnitude of the observed direct associations between the number of ACEs and incident health-professional diagnosed migraine are consistent with the associations reported in the other pediatric studies. [3][4][5][6] Because the number of adverse events tapered off quickly following two, we could not examine associations beyond two or more stressors.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similarly, others have observed cross-sectional relationships between the number of ACEs and headache but did not investigate migraine independently. 5,6 Within the present study, the magnitude of the observed direct associations between the number of ACEs and incident health-professional diagnosed migraine are consistent with the associations reported in the other pediatric studies. [3][4][5][6] Because the number of adverse events tapered off quickly following two, we could not examine associations beyond two or more stressors.…”
Section: Discussionsupporting
confidence: 92%
“…5,6 Within the present study, the magnitude of the observed direct associations between the number of ACEs and incident health-professional diagnosed migraine are consistent with the associations reported in the other pediatric studies. [3][4][5][6] Because the number of adverse events tapered off quickly following two, we could not examine associations beyond two or more stressors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Further limitations among the morass of cross-sectional studies in adults included incomplete characterization of types, frequency, and temporal sequence of ACEs and headache. Studies of ACEs and headache in children and adolescents are fewer, [10][11][12][13][14][15][16][17] and although they minimize some of the limitations of adult studies, potential obstacles to getting valid information remain. Youthful participants, for instance, may be reluctant to report abuse due to fear of punishment or rejection, and their parents may deny maltreatment because they are unaware, or wish to shield themselves or perpetrators in the household from blame, thus leading to underestimation of the prevalence of ACEs.…”
mentioning
confidence: 99%